The Devils - Huxley, Aldous 1894-1963; Whiting, John Robert 1917-1963 (British Film Institute, 2012)
"In seventeenth-century France, Father Urbain Grandier (Oliver Reed) uses his power to protect the city of Loudun from destruction at the hands of the establishment. Soon, he stands accused of the demonic possession of Sister Jeanne (Vanessa Redgrave), whose erotic obsession with him fuels the hysteria that sweeps through her convent. [...] The devils stands as a profound commentary on religious hysteria, political persecution and the corrupt marriage of church and state."
Verlagsnummer: BFIVD940
Original: UK 1971
Original aspect ratio 2.35:1
DISC ONE: DVD premiere presentation of the original UK "X" certificate version, Mark Kermode introduction (2012, 2 min): the broadcaster and critic's newly filmed foreword to The Devils, audio commentary with Ken Russel, Mark Kermode, Michael Bradsell and Paul Joyce, Original UK trailer, Original US trailer, Amelia and the Angel (Ken Russell, 1958, 26 min): a delightful mix of religious allegory and magical fantasy; DISC TWO: Hell on Earth (Paul Joyce, 2002, 48 min): documentary exploring the film's production and controversial history, Director of devils(1971, 22 min): documentary featuring candid Ken Russell interviews and unique footage of Sir Peter Maxwell Davies recording his score, On-set footage with Michael Bradell commentary(2012, 8 min), On-stage Q&A with Ken Russell(2012, 13 min): the director in conversation with Mark Kermode at the NFT in 2004; also includes a fully illustrated booklet featuring new essays by Mark Kermode, Craig Lapper and editor Michael Bradsell, with original production materials and on-set photographs
Keywords: DVD-Video